Propriedades hídricas e mecânicas de neossolos e saprolitos vulcânicos no sul do Brasil - Deobald, Gabriel Antônio (2017)
The Regosols are shallow soils that have a saprolite horizon (Cr) below an A horizon. Saprolite materials and soils are often used for engineering purpose without adequate information about their properties. Are soils that have limitations related to the effective depth, so it is important to know their hydraulic behavior to promote their sustainable use. Meet your water and geotechnical behavior is critical to identify the potential use and use in a sustainable way. The objective of this work was to study soil and saprolites of Regosols derived from volcanic rocks of the Serra Geral Formation, in order to evaluate the influence of weathering, mineralogical and morphological constitution in their physical properties, geotechnical and water. The work was carried out in eight profiles derived from basic and acidic volcanic rocks of the Serra Geral Formation. The morphology, particle size, porosity, density, saturated hydraulic conductivity, water retention, organic carbon, chemical dissolution, x-ray diffractometry, x-ray proctor test standard, consistency and uniaxial compression the 6 and 10 kPa were evaluated. The results showed that saturated hydraulic conductivity is higher on the horizon the most profiles. The horizons Cr of Regosols presented water retention than the horizons to even. The layers RCr presented low density, high porosity and high water retention, indicating the formation of pores already in the early stages of alteration of rock. Geotechnically, attributes such as clay and carbon affected the samples in a variable way, without the standard behavior. The acidity from the rock and mineralogy of horizons did not affect the geotechnical behavior of the samples.